Sosialisasi dan Pendampingan Pemanfaatan Media Sosial Sebagai Sarana Dakwah Remaja Masjid di Dusun Mulyorejo Kampung Baru - Laila Agustina Fahmi; Lailatul Qomariyah (LP3M IAIFA Kediri, 2022)
Advances in information technology provide many new variations in social relations where every person who wants to interact does not need to meet in person and this is a means of changing the way of Islamic da'wah quickly and flexibly. The convenience of the internet network is an advantage that can be used as an alternative means of preaching. The convenience of the facilities provided by social media is a distinct advantage for the community, especially for da'wah interpreters or da'wah actors to share information about Islam. Social media in fact also has a positive and negative impact if someone uses it with good things. The purpose of this research is to dig deeper and understand about the use and forms of Islamic da'wah that can be done through social media. Determination of data sources is done by means of observation, interviews and documentation. Da'wah on social media is now increasingly widespread, especially among teenagers, marked by the emergence of poster works, virtual studies of science, as a medium for preaching. Because millennials use social media a lot and have extraordinary power to make content viral and realize that this is the era of audio visuals